PREVALENCE OF PHARYNGEAL AND RECTAL CHLAMYDIA TRACHOMATIS AND NEISSERIA GONORRHOEAE INFECTIONS AMONG MSM IN SOFIA, BULGARIA - Ivva Philipova; Elena Birindjieva; Alexander Milanov; Savina Stoitsova (Problems of Infectious and Parasitic Diseases, 2022)
Abstract: Sexually transmitted infections (STIs) caused by Chlamydia trachomatis and Neisseria gonorrhoeae continue to be a major public health problem. Although they mainly affect the urogenital tract, N. gonorrhoeae and C. trachomatis can also be found in the pharynx and rectum. As data on extragenital chlamydia and gonorrhea in Bulgaria are still scarce, this study aimed to (1) determine the prevalence of pharyngeal and rectal infections with C. trachomatis and N. gonorrhoeae among men who have sex with men (MSMs) from Sofia and (2) to identify risk factors related to these infections to support screening recommendations based on scientific evidence. One hundred and fifteen MSM aged 16-50 were tested by systematic sampling during a visit to a sexual health center for voluntary and confidential HIV testing in Sofia. A questionnaire was used to collect demographics and risk factors, and clinical material from three anatomical sites: pharynx, rectum, and urogenital tract (first void urine or urethral swab) was examined to detect C. trachomatis and N. gonorrhoeae infections. The prevalence of C. trachomatis was 8.7% in the rectal samples tested, and the prevalence of N. gonorrhoeae was 0.9% and 5.2% in the pharyngeal and rectal samples, respectively. Local symptoms were reported in only 16.6% of rectal gonococcal infections and in 20% of C. trachomatis rectal infections. Patients reporting multiple partners had a significantly higher risk of being positive (OR = 3.8, 95% CI 1.03-14). The risk of HIV-positive MSM and those having unsafe sex was also higher (OR = 1.9 95% CI 0.19-20 and OR = 4.6 95% CI 0.98-21, respectively), but the findings were not statistically significant. Overall, more than 80% of extragenital infections would remain undetected and therefore transmissible if only symptomatic cases were investigated. These results suggest that in Bulgaria HIV-positive MSM and those having multiple sexual partners and unprotected sex would benefit from screening for extragenital STIs. Larger sample surveys could provide a better characterization of risk factors to guide screening choices.